Early osteoblast responses to orthopedic implants: Synergy of surface roughness and chemistry of bioactive ceramic coating. Issue 6 (24th September 2014) - Aniket; Reid, Robert; Hall, Benika; Marriott, Ian; El‐Ghannam, Ahmed
Abstract Pro‐osteogenic stimulation of bone cells by bioactive ceramic‐coated orthopedic implants is influenced by both surface roughness and material chemistry; however, their concomitant impact on osteoblast behavior is not well understood. The aim of this study is to investigate the effects of nano‐scale roughness and chemistry of bioactive silica‐calcium phosphate nanocomposite (SCPC50) coated Ti‐6Al‐4V on modulating early bone cell responses. Cell attachment was higher on SCPC50‐coated substrates compared to the uncoated controls; however, cells on the uncoated substrate exhibited greater spreading and superior quality of F‐actin filaments than cells on the SCPC50‐coated substrates. The poor F‐actin filament organization on SCPC50‐coated substrates is thought to be due to the enhanced calcium uptake by the ceramic surface. Dissolution analyses showed that an increase in surface roughness was accompanied by increased calcium uptake, and increased phosphorous and silicon release, all of which appear to interfere with F‐actin assembly and osteoblast morphology. Moreover, cell attachment onto the SCPC50‐coated substrates correlated with the known adsorption of fibronectin, and was independent of surface roughness. High‐throughput genome sequencing showed enhanced expression of extracellular matrix and cell differentiation related genes. These results demonstrate a synergistic relationship between bioactive ceramic coating roughness and material chemistry resulting in a phenotype that leads to early osteoblast differentiation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1961–1973, 2015.